Compatibility Implementation Plan for Xi’an Metro Line 2 Phase Ⅰ and Phase Ⅱ Project Signaling Systems - SUN Hui; REN Yaping; LIANG Bo (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] The signaling system for Xi’an Metro Line 2 Phase Ⅰ project (hereinafter referred to as Line 2) utilizes an imported system, while Phase Ⅱ adopts a domestically developed system. The Phase Ⅱ project is an extension line of Phase Ⅰ, and the signaling systems of both must be fully interoperable to enable seamless operations. Additionally, Phase Ⅱ must enhance the functionality and performance based on the existing Phase Ⅰ project. Therefore, it is necessary to conduct a targeted study on the compatibility implementation plan for the signaling systems across the two phases. [Method] Based on an overview of the compatibility implementation strategy, specific compatibility solutions are designed for key subsystems, including the ATS (automatic train supervision) subsystem, interlocking subsystem, wayside ATP (automatic train protection) subsystem, on-board ATP/ATO (automatic train protection/operation) subsystem, and DCS (data communication subsystem). A compatibility test environment is constructed on the test track and the main line of Line 2, and one train is retrofitted with domestically developed on-board equipment to verify the compatibility solution effectiveness for the proposed Line 2 signaling system after implementation. [Result & Conclusion] The compatible implementation plan successfully enables the safe and reliable interoperation between phase Ⅰ and Ⅱ project signaling systems, while significantly enhancing the signaling system overall performance. Following the implementation, the operational efficiency of Line 2 is significantly improved.